การพัฒนาแบบวัดความเหนื่อยหน่ายของครูประถมศึกษา - โศภิต พุฒขาว (จุฬาลงกรณ์มหาวิทยาลัย, 1997)
To develop the elementary school teachers burnout scale. The developed test consisted of 2 parts measuring 2 dimensions of burnout. The checklist part consisting of 7 items was constructed to measure the behavioral dimension and the multiple-choice part consisting of 25 items was constructed to measure the feeling dimension. The 509 elementary school teachers from the educational region six were the samples. The results were as follows: 1.The internal consistency of the developed test of the first and second part was .3024 and .9415 respectively. 2. The discriminant validity of the developed test analyzed by testing difference of mean scores between high and low burnout teacher groups was significantly different at .01 level. 3. The construct validity of the developed test analyzed by using exporatory factor analysis approach showed 4 factors. These 4 factors were Emotional Exhaustion, Physical Exhaustion, Depression and Frustration from work. The four-factor model was confirmed by the confirmatory factor analysis.